2015
DOI: 10.1177/0276236615574488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Image and Verbal Generation on False Memory

Abstract: The effects of image and verbal generation on false memories in the Deese–Roediger–McDermott (DRM) paradigm were investigated by comparing three experimental conditions (description, image, and image description). False memory rates were reduced when participants received an explicit imagery instruction rather than when they were asked to describe the characteristics of word referents or both imagine and describe referents. Verbal generation is thought to promote the associated processing of list items and thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…Our findings revealed false memories effect in DRM and misinformation tasks replicating previous studies (Roediger & McDermott, 1995;Loftus et al, 1978). We found that imaging instruction reduced DRM false memories in line with past findings (Foley, 2012;2006;Gunter et al, 2007;Robin, Ménétrier, & El Haj, 2019;Robin & Mahé, 2015;Robin, 2011;2010). In contrast, it was not possible to conclude that the imaging instruction decreases or increases false memories in the misinformation task.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings revealed false memories effect in DRM and misinformation tasks replicating previous studies (Roediger & McDermott, 1995;Loftus et al, 1978). We found that imaging instruction reduced DRM false memories in line with past findings (Foley, 2012;2006;Gunter et al, 2007;Robin, Ménétrier, & El Haj, 2019;Robin & Mahé, 2015;Robin, 2011;2010). In contrast, it was not possible to conclude that the imaging instruction decreases or increases false memories in the misinformation task.…”
Section: Discussionsupporting
confidence: 90%
“…These results replicated those found in previous studies showing a constant reduction in false memories with an imaging instruction (Burns, Jenkins, & Dean, 2007, exp.2;Foley, 2012;Foley Wozniak, & Gillum, 2006;Gunter, Bodner, & Azad, 2007;Olszewska & Ulatowska, 2013;Perez-Mata, Read, & Diges, 2002;Robin & Mahé, 2015;Robin et al, 2019).…”
Section: Bayesian Analysessupporting
confidence: 89%
See 2 more Smart Citations
“…Instead of being asked to “write” the words in half of the DRM sets, participants were asked to “imagine” how the object that the word represents looks. As such, half of the prompt words were “draw” and half were “imagine.” In addition, they were asked to make a rating regarding how easily they could bring to mind a vivid mental image for each of the words in a set, an instruction based on previous work assessing the effects of imagery at encoding (Robin, 2011; Robin & Mahé, 2015). The specific instructions given for the “imagine” task were as follows:Create a mental image of the object that the word represents.…”
Section: Methodsmentioning
confidence: 99%